Literatuur en muziek / Literature and Music - Arteel, Inge; Forment, Bruno (Academia Press, 2018)
Litaerature and music are two media of artistic expression that have a longstanding connection in cultural history. Today, more than ever, there are diverse experiments with hybrid forms that positively exploit the differences and links between both art forms. The contributions to this issue reflect the diverse nature of the relation between literature and music and the methodological diversity of the research.